2011
DOI: 10.1111/j.1365-2362.2011.02573.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver dysfunction in chronic heart failure: prevalence, characteristics and prognostic significance

Abstract: Liver dysfunction is frequent in CHF and characterized by a predominantly cholestatic enzyme profile that is associated with disease severity and prognosis. Thus, we propose a cardio-hepatic syndrome in CHF. Future studies are needed to clarify the exact mechanisms of organ interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
118
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(125 citation statements)
references
References 41 publications
4
118
2
1
Order By: Relevance
“…In a study that evaluated patients with acute decompensated heart failure, 36.1% had an elevated bilirubin level 28. In another study that involved ambulatory patients with heart failure, bilirubin was elevated in 15.2% of patients 29. Although it is conceivable that the prevalence of ductal enzyme elevation varies in different cardiac conditions, our study revealed that almost half of the patients with TR awaiting TA had an elevated bilirubin level (49%).…”
Section: Discussionmentioning
confidence: 47%
“…In a study that evaluated patients with acute decompensated heart failure, 36.1% had an elevated bilirubin level 28. In another study that involved ambulatory patients with heart failure, bilirubin was elevated in 15.2% of patients 29. Although it is conceivable that the prevalence of ductal enzyme elevation varies in different cardiac conditions, our study revealed that almost half of the patients with TR awaiting TA had an elevated bilirubin level (49%).…”
Section: Discussionmentioning
confidence: 47%
“…In addition, in the current study DILIsym was not parameterized for heart failure patients. While liver function test (LFT) abnormalities are common in heart failure patients, little is currently known about the effects of heart failure on hepatic function 19, 20, 21. In the current study the subjects had normal baseline LFTs.…”
Section: Discussionmentioning
confidence: 87%
“…This can be explained by hepatic congestion due to increased venous pressure resulting in cholestasis and elevated ALP and Bilirubin. However elevated cholestatic enzymes in the absence of right heart involvement is puzzling although this was noted in the study carried out by Poelzl et al [17]. In their cohort consisting of 1032 patients with chronic heart failure the predominant abnormality was elevation in cholestatic enzymes.…”
Section: Discussionmentioning
confidence: 82%